Pemanfaatan Aplikasi Satu Sehat oleh Remaja dalam Pemantauan Kesehatan Pribadi di SMK Ma’arif NU 2 Ajibarang - Iis Sumiyati; Retno Handayani (Journal of Innovative and Creativity, 2026)
This study aims to determine how the Satu Sehat application is used among teenagers. This design uses a quantitative descriptive method, with the respondents in this study being students at SMK Ma'arif NU 2 Ajibarang. The population consists of 1,102 samples obtained using the Slovin formula with a 5% margin of error, resulting in 294 respondents. The data is from 2025. Respondents were selected using stratified random sampling. In grade 10, 3 classes were selected from 36 students; in grade 11, 3 classes were selected from 30 students; and in grade 12, 3 classes were selected from 30 students. The instrument used was a 20-question questionnaire with a 4-point Likert scale, which had been tested for validity and reliability. From the results of a study conducted on 294 respondents at SMK Ma'arif NU 2 Ajibarang, it was found that 52 respondents (18%) felt that the use of the Satu Sehat app provided benefits in monitoring personal health. Meanwhile, 241 respondents (82%) felt that the Satu Sehat app had not yet provided significant benefits for them. It is recommended that education and awareness campaigns be conducted within the school environment to encourage teenagers to be more active in monitoring their personal health conditions through digital technology.